Introduction - Morgan, Hywel; Rout, Chandra S.; Late, Dattatray J. (Fundamentals and Sensing Applications of 2D Materials, 2019)
The book provides comprehensive and updated research contribution about advances in synthesis/growth of 2D materials for various sensor applications, their working principles, and mechanism behind the sensor as well physics and chemistry of materials.